Comparison of the efficacy of the Epley maneuver and repeated Dix–Hallpike tests for eliminating positional nystagmus: A multicenter randomized study - Takao Imai; Takao Imai; Atsuhiko Uno; Akiyuki Yamato; Yasumitsu Takimoto; Yasumitsu Takimoto; Go Sato; Kazunori Matsuda; Noriaki Takeda; Suetaka Nishiike; Kayoko Kawashima; Tomoko Iga; et al. (Frontiers in Neurology, 2023)
Background and objectivesPatients with benign paroxysmal positional vertigo of the posterior canal (pc-BPPV) exhibit BPPV fatigue, where the positional nystagmus diminishes with the repeated performance of the Dix–Hallpike test (DHt). BPPV fatigue is thought to be caused by the disintegration of lumps of otoconial debris into smaller parts and can eliminate positional nystagmus within a few minutes [similar to the immediate effect of the Epley maneuver (EM)]. In this study, we aimed to show the non-inferiority of the repeated DHt to the EM for eliminating positional nystagmus after 1 week.MethodsThis multicenter, randomized controlled clinical trial was designed based on the CONSORT 2010 guidelines. Patients who had pc-BPPV were recruited and randomly allocated to Group A or Group B. Patients in Group A were treated using the EM, and patients in Group B were treated using repeated DHt. For both groups, head movements were repeated until the positional nystagmus had been eliminated (a maximum of three repetitions). After 1 week, the patients were examined to determine whether the positional nystagmus was still present. The groups were compared in terms of the percentage of patients whose positional nystagmus had been eliminated, with the non-inferiority margin set at 15%.ResultsData for a total of 180 patients were analyzed (90 patients per group). Positional nystagmus had been eliminated in 50.0% of the patients in Group A compared with 47.8% in Group B. The upper limit of the 95% confidence interval for the difference was 14.5%, which was lower than the non-inferiority margin.DiscussionThis study showed the non-inferiority of repeated DHt to the EM for eliminating positional nystagmus after 1 week in patients with pc-BPPV and that even the disintegration of otoconial debris alone has a therapeutic effect for pc-BPPV. Disintegrated otoconial debris disappears from the posterior canal because it can be dissolved in the endolymph or returned to the vestibule via activities of daily living.Classification of evidenceThis study provides Class II evidence of the non-inferiority of repeated DHt to the EM for eliminating positional nystagmus after 1 week.Registration numberUMIN000016421.